Pencegahan Zina dalam Perspektif Maqāṣid al-Syarī‘ah Kitab Fathul Muin: Studi Implementatif pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Prevention of Adultery from the Perspective of Maqāṣid al-Syarī‘ah of the Book of Fathul Muin: Implementation Study on Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Rafiq Naufal Mufid; Dendra Yoga Pratama; Abdan Syakur; Febrian Putra; Gilang Ananda Fidaus; Alifudin Ahnan; Harits Fida’ Imadudin (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This research discusses the prevention of adultery from the perspective of maqāṣid al-syarī'ah by referring to the Book of Fathul Mu'in by Sheikh Zainuddin al-Malibari and its implementation in book subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. Adultery is a major sin that not only impacts the perpetrator, but also damages the social structure, heredity and community honor. Within the framework of maqāṣid al-syarī'ah, the prohibition of adultery aims to protect religion, soul, mind, property, and especially offspring (ḥifẓ al-nasl) and honor (ḥifẓ al-'irḍ). The book Fathul Mu'in provides a comprehensive fiqh explanation regarding social boundaries, guarding one's views, prohibiting seclusion, and self-control etiquette as part of prevention efforts. Thus, Islamic boarding schools function not only as centers for the transmission of knowledge, but also as moral fortresses that maintain the integrity and personal purity of students.